Anti-hyperalgesic effect of paracetamol in rat model of thermal hyperalgesia: implications for the treatment of neuropathic pain - Bankar, Mangesh A.; Dudhgaonkar, Sujata S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Neuropathic pain conditions are prevalent in general population and difficult to treat. Most currently available therapies do not provide adequate benefit in all treated patients. Though Paracetamol is available for more than 100 years and have huge safety data, it is still not included in any treatment guidelines for neuropathic pain, as very few studies have evaluated its effects in neuropathic pain conditions. The aim of this study was to evaluate antihyperalgesic activity of paracetamol and to compare it with antihyperalgesic effect of amitriptyline and gabapentin in rat model of thermal hyperalgesia. Methods: Male albino wistar rats weighing 200-250 g of body weight and 4-6 months old were used. After anaesthetizing rats with 2% halothane, mild thermal injury was induced using hot plate analgesiometer. Drugs were administered intraperitoneally 30 minutes after thermal injury. Paw withdrawal latencies were measured at 30, 60, 90 and 120 minutes after drug administration. Statistical analysis done using GraphPad Prism version 5.01 and one way ANOVA followed by post hoc Dunnett’s test or Tukey’s test were used. Results: Paracetamol showed both dose as well as time dependent antihyperalgesic activity. Gabapentin demonstrated significantly more antihyperalgesic activity compared to amitriptyline (p< 0.05) and paracetamol (p< 0.01). Conclusions: Paracetamol showed antihyperalgesic activity however, it was less as compared to drugs like gabapentin and amitriptyline. Considering the excellent safety profile of paracetamol, it might be useful adjuvant drug for treatment of neuropathic pain conditions.